The effects of text reminders on the use of family planning services: Evidence from a randomised controlled trial in urban Mozambique - Leight, Jessica; Hensly, Catherine; Chissano, Marcos; Safran, Elana; Ali, Liza; Dustan, Domingos; Jamison, Julian (BMJ, 2022)
Introduction: Reduction of unmet need for contraception is associated with enhanced health outcomes. We conducted a randomised controlled trial in Mozambique analysing the effects of text messages encouraging use of family planning services. Methods: This trial was conducted within a sample of women served by the Integrated Family Planning Program implemented by Population Services International, in which community health workers provide clinic referrals for family planning services. The evaluation enrolled 5370 women between 20 January and 18 December 2020 who received a referral, reported access to a mobile phone and provided consent. Women were randomly assigned to a treatment group that received a series of text message reminders encouraging them to visit a clinic or to a control arm. An intention-to-treat analysis was conducted to analyse the effect of reminders on the probability of a clinic visit and contraceptive uptake. The final analysis includes 3623 women; 1747 women were lost to follow-up. Results: Women assigned to receive the text reminders are weakly more likely to visit a clinic (risk difference 2.3 percentage points, p=0.081) and to receive a contraceptive method at a clinic (2.2 percentage points, p=0.091), relative to a base rate of 48.0% and 46.9%, respectively. The effect on clinic visits is larger and statistically significant in the prespecified subsample of women enrolled prior to the COVID-19-related state of emergency (3.2 percentage points, p=0.042). Conclusion: Evidence from this trial suggests that text message reminders are a promising nudge that increases the probability that women receive contraception.